Numerical and experimental investigations of twin-engine-light utility helicopter wake flow - Stuhlpfarrer, M.; Kümmel, A.; Steck, J.; Breitsamter, C. (My University, 2015)
The present paper concentrates on the unsteady characteristics of the wake flow field emanating from a helicopter fuselage and rotor head. Predicting the convection of blade tip vortices and other coherent structures generated by the fuselage and the rotor head is difficult by applying numerical methods. Therefore, numerical and experimental investigations have been carried out on a twin-engine-light utility helicopter to provide a data base for code validation. The wind tunnel model includes a fuselage and a rotating five-bladed rotor head. The latter allows cyclic and collective pitch motion. The numerical investigations are performed with ANSYS Fluent. The flow solver is based on the unsteady Reynolds-averaged Navier-Stokes equations. Turbulence modelling is performed with the shear stress transport model and the scale adaptive simulation model.
Keywords: Aircraft Design